State resilience and rate of recovery among addicts: Moderating role of social skills - Abbasi, Najam ul Hasan; Muhammad, Saghir (Frontiers in Psychiatry, 2022)
The present study intended to explore the moderating role of social skills in State Resilience and the rate of recovery among drug addicts. The sample size was 100 recovering addicts from different drug rehabilitation centers were recruited from twin cities (Islamabad and Rawalpindi) of Pakistan. The Social Skills Inventory (SSI) was used to assess social skills, while Connor-Davidson Resilience Scale (CD-RISC) and Substance Use Recovery Evaluator (SURE) was used to assess state resilience and recovery among study participants. Results suggest a significant positive correlation between social skills and recovery (r=.27; (p<.01). Similarly, state resilience was found to be significantly correlated with social skills (r=.35; (p<.01), while state resilience was not significantly correlated with recovery. The moderation analysis for the interaction of social skills on state resilience was non-significant (β = .002, 95% CI [-.002, .00], t=1.01, p= .316). Results also indicate the significant relationship of social skills in the prevention of relapse against drug use.